Characteristic Test of Bioethanol Made from Leftover Fruit (Food Material After Ceremony) Using Yeast (Saccharomyces cerevisiae) - Muliarta, I Nengah; Setianingsih, Ni Luh Putu Putri; Sudiarta, I Wayan; Putra, I Ketut Suwarmadi; Dusak, Putu Gede Bayu Janardhana (PT FORMOSA CENDEKIA GLOBAL, 2024)
Bioethanol can be produced from plants that contain a lot of starch and cellulose compounds by using the help of yeast activity from fruit skin waste. Sugar compounds in fruits are usually a mixture of glucose and fructose. Fruits contain carbohydrates, glucose, and fructose, so fruits have great potential to be raw materials for bioethanol. The study results obtained bioethanol with a long fermentation time of up to the fifth day with different yeast concentrations, namely 2%, 4%, 6%, 8%, and 10%. The maximum bioethanol concentration results were produced by a concentration of 6% S. cerevisiae, namely 8.17%, the content because the addition of yeast is by the amount of nutrients in the sample.